دور مصلحة الأحوال المدنية في التطوير الإداري - عوند. بشير مسعود (Aljameai, 2024)
المستخلص: يعتبر موضوع التطوير الإداري من المواضيع الجديرة بالاهتمام والبحث والدراسة، وقد لاقى موضع اهتمام الباحثين والمفكرين على المستويين الدولي والمحلي، فكل مؤسسة تحتاج إلى تطوير إداراتها وإمكاناتها المادية والبشرية. وقد لعبث مصلحة الأحوال المدنية دوراً ايجابيًا في رسم السياسة العامة للدولة الليبية، من خلال منظومة الرقم الوطني، وهذا إن دل على شيء إنما يدل على تطوير إدارتها. فضرورة نشر وتعميم الثقافة الإلكترونية والتحول الرقمي يعد سمة من سمات التطورات الحديثة في عالمنا المعاصر، فلابد من سن تشريعات قانونية فاعلة قادرة على خلق تطوير إداري نجاعة في عملية مواكبة التغيرات الاقتصادية والاجتماعية والسياسية. فتبسط الإجراءات وسرعة إنجاز الأعمال وتطويرها يساهم في خلق تطوير إداري فعالاً. فالتخطيط السليم والبيئة المناسبة والنظرة الشمولية كلها مقومات فعّالة للتطوير الإداري. Abstract: The subject of administrative development is one of the topics worthy of attention, research and study, and it has attracted the attention of researchers and thinkers at the international and local levels. Every institution needs to develop its departments and its material and human capabilities. The Civil Status Authority played a positive role in drawing up the general policy of the Libyan state, through the national number system, and this, if anything, indicates the development of its administration. The necessity of disseminating and disseminating electronic culture and digital transformation is a feature of recent developments in our contemporary world. Effective legal legislation must be enacted capable of creating efficient administrative development in the process of keeping pace with economic, social and political changes. The simplification of procedures and the speed of completion and development of works contribute to the creation of effective administrative development. Proper planning, an appropriate environment, and a holistic view are all effective ingredients for administrative development.